Speech Acts in English Translation of Quran Surah Al-Fatihah and Surah Al-A’laa By Abdullah Yusuf Ali - Liza Mariska; Iwan Kurniawan; Dian Reftyawati (Jurnal Pendidikan Indonesia, 2022)
Background: Language is important for people in communication. Starting the communication, people have to understand what the speaker is saying and what is being said. In this case, the speech act theory of learning is important to overcome this problem. Objective: The purpose of this study was to find out the types of acts used in the translation of Abdullah Yusuf Ali's surah al-fatihah and al-alaa through reading and then describe the speech acts based on the type and classification of functions in the text. translation of surah al fatihah and surah. al-alaa by Abdullah Yusuf Ali. Methods: This study uses qualitative methods and Austin theory to determine the types of speech acts, the meaning of speech acts, and the function of speech acts in the translation of Al-Quran Surah Al-Fatihah and Surat Al-A'laa. , and the data collected is in the form of words instead of numbers. This study uses document sources to find research sources. speech act with Austin theory. The data source is by looking at several books and translations of the Koran by Abdullah Yusuf Ali as objects containing linguistic phenomena, especially aspects of speech acts. This research was conducted in 3 ways: interview, observation, and document analysis or artifact analysis. Results: Speech act is an activity in which participants interact with conventional language to achieve a result that involves two parties, namely the speaker and the speech partner in one main speech, in time, place, and speech situation. Conslusion: This study identifies 7 verses in Surah al-Fatihah and 19 verses in Surat Al-Alaa in Abdullah Yusuf Ali's translation of the Koran, in Surah Al-Fatihah there are 7 types of locutions, 18 illocutions with 6 functions. assertive, 4 directive, 1 commissive, 3 expressive, 5 declarative, and 7 perlocutionary sentences. Surah Al-Alaa contains 19 types of locutions, 31 illocutions with 8 assertive functions, 6 directives, 3 commissives, 1 expressive, 13 declarative sentences, and 19 perlocutionary sentences.